Implementing Universal Design for Learning (UDL) in Higher Education: A Case Study of Teacher Experiences in Private High Schools in Dubai - SALEH, ABDELWAHB YEHIA (2024)
This study explores the implementation of Universal Design for Learning (UDL) principles in high school education within the context of Dubai. By examining the experiences of high school teachers and student outcomes, the research aims to understand the strategies used, challenges faced, and benefits perceived in applying UDL principles. Using a mixed-methods approach, the study combines quantitative data from a survey with qualitative insights from interviews. The findings indicate that teachers in Dubai are incorporating UDL principles to varying degrees, with a strong emphasis on multiple means of engagement. Despite challenges such as limited resources and insufficient professional development, the implementation of UDL has led to increased student engagement, improved academic performance, and greater inclusivity. The study concludes that UDL has significant potential to enhance educational practices in Dubai's diverse and multicultural context. Recommendations for practice include increasing resource availability, providing ongoing professional development, fostering collaborative planning, ensuring administrative support, and engaging students and the community. Future research should focus on longitudinal studies, cross-cultural comparisons, the impact on specific student populations, qualitative methodologies, and the integration of technology in UDL implementation.